Immunodiagnosis and vaccination for brugian filariasis: direct rewards from research investments - Abdullah, Wan Omar (2002)
Lymphatic filariasis is a field that has undergone a rapid expansion of knowledge, the direct reward of research investments made over the past 20 years. These advances have included the diagnosis of infection and monitoring of control efforts that have been made feasible by the development of tools based on antigen and DNA detection. The most important of the new tools for the control of lymphatic filariasis are simple, safe, inexpensive, conveniently delivered drugs that kill the microfilariae and adult worms. New diagnostic tools such as lymphoscintigraphy and ultrasonography for the examination and identification of hidden damage have also been developed that are far easier to use than anything previously. However, it is inopportune to conceive that problems of diagnosis of lymphatic filariasis as completely solved when there is still no antigen tests for the diagnosis of active or current infection with Brugia malayi. Brugian filariasis is zoonotic whereby man and animal reservoirs share the infection and is transmitted by the same species of mosquito vectors that are both zoophilic and anthropophylic. In endemic areas of subperiodic B. malayi where animal reservoir of the infection exists, filariasis control programme were adversely affected. Vaccination may form the basis of a possible future control method of public health importance in the elimination of microfilariae in animal reservoirs that would break the zoonotic transmission. Universiti Putra Malaysia in a deliberate attempt to join the international scientific community toward the control and possible eradication of lymphatic filariasis has embarked on research into the development of antifilarial nucleic acid vaccine i.e. to genetically engineered vaccines that can block zoonotic transmission of brugian filariasis. Filaricidal drugs unfortunately has no effect on the main pathological consequence of repeated infection, namely elephantiasis, for which in fact no drug treatment has any effect except possibly steroids in early cases. At Universiti Putra Malaysia, small scale preliminary studies into herbal remedy for chronic elephantiasis has been conducted and has shown encouraging results. Such herbal remedy undoubtedly will be of great service in restoring dignity, respect and health to the patients. Investment into this new research paradigm is therefore highly recommended. All these are exciting research findings but still more newer important scientific discoveries are still yet to come which will have far reaching implications for the future control of lymphatic filariasis and potentially its eradication.